Shape and Level Bottles Detection Using Local Standard Deviation and Hough Transform - Nor Nabilah Syazana Abdul Rahman; Norhashimah Mohd Saad; Abdul Rahim Abdullah (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper presents shape and level analysis using local standard deviation and Hough transform technique to detect the shape and level of the bottle.A 155 sample images are used as a test product to detect shape and level. Local standard deviation is used contrast gain technique to segment the shape of the bottle by enhancing the contrast of the image. The ratio of the area is calculated from the extent parameter. The maximum and minimum water level is created by using Hough transform technique to identify the level of the water. Decision tree is applied to classify the shape and level of the bottle either good or defect condition. From experimental result, 97% and 93% accuracy of shape and level is achieved which shows that the proposed analysis technique is potential to be applied for beverages product inspection system.